The Impact of Online Customer Reviews on Purchasing Decisions of Vocational College Students on Tokopedia Platform - Nasywa Firyali Saniyah (Asosiasi Ahli Administrasi Indonesia, 2023)
This study explores the impact of online customer reviews on the purchasing decisions of vocational students, using Tokopedia as the research object. In the context of rapid growth in online shopping, consumer trust in e-commerce platforms is crucial for decision-making. A descriptive method with a quantitative approach was employed, and data were collected through questionnaires distributed to 130 vocational students. The results of simple regression analysis indicate that approximately 23.9% of the variation in purchasing decisions can be explained by the variation in online customer reviews on Tokopedia. This finding emphasizes the significant role of customer reviews in building trust and influencing purchasing decisions. The implications suggest that sellers should focus on product quality, customer service, and review management to maintain consumer trust. These findings provide insights for e-commerce platforms and researchers to continually enhance the online shopping experience and understand the factors influencing consumer purchasing decisions.